2019
DOI: 10.1155/2019/2357217
|View full text |Cite
|
Sign up to set email alerts
|

Jieduquyuziyin Prescription-Treated Rat Serum Suppresses Activation of Peritoneal Macrophages in MRL/Lpr Lupus Mice by Inhibiting IRAK1 Signaling Pathway

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease, and Jieduquyuziyin prescription (JP) is a traditional Chinese medicine (TCM) formula that has been testified to be effective for SLE treatment as an approved hospital prescription for many years in China. However, its mechanism of action in the treatment of this disease is largely unknown. The purpose of this study was to determine whether JP-treated rat serum can inhibit the activation of peritoneal macrophages in MRL/lpr mice by downregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Ji et al tested both Sprague Dawley rats in addition to MRL/lpr mice. Ji et al found that JP treatment inhibited phosphorylation of IRAK1 and its downstream proteins induced by LPS ( Ji et al, 2019b , 2020 ). JP also inhibited the expression of TNF and IL-6 and reduced peritoneal macrophage activation.…”
Section: Results and Context Of Included Studiesmentioning
confidence: 99%
“…Ji et al tested both Sprague Dawley rats in addition to MRL/lpr mice. Ji et al found that JP treatment inhibited phosphorylation of IRAK1 and its downstream proteins induced by LPS ( Ji et al, 2019b , 2020 ). JP also inhibited the expression of TNF and IL-6 and reduced peritoneal macrophage activation.…”
Section: Results and Context Of Included Studiesmentioning
confidence: 99%
“…And it is valuable to inhibit the IRAK1 signaling pathway to reduce the inflammatory cascade-mediated tissue damage [ 27 ]. In the previous study, we used lentiviral transfection technology to overexpress shRNA with IRAK1 to prove that TCM reduced IRAK1 expression in peritoneal macrophages of MRL/lpr mice [ 36 ]. Thus, we evaluated IRAK1 expression levels in vivo and in vitro to further understand its role in the inflammatory pathway through gene and protein detection experiments.…”
Section: Resultsmentioning
confidence: 99%
“…JP was composed of 10 herbs ( Table 1 ) which were mixed according to the mass ratio 5:4:4:5:4:5:4:3:3:2 ( Ji et al., 2019a ). Among them, Rehmannia glutinosa (Gaertn.)…”
Section: Methodsmentioning
confidence: 99%